knowing others' preferences degrades the quality of group decisions. [article]. - Mojzisch, Andreas
Results from the experiments demonstrate that learning the other group members' preferences at the beginning of a discussion impedes the solution of hidden profiles. In experiment 1-3, participants who were not informed about their fellow group members' preferences were more likely to solve a hidden profile than those who received bogus information about the others' preferences. The negative effect of learning the others' preferences on decision quality was mediated by participants paying less attention to the information exchanged when they had been made aware of the others' references. Experiment 1 and 2 further ruled out the effect of learning the others' preferences is due to participants bolstering their position or due to an increase in informational load. Experiment 3 showed that learning the other group members' preferences impedes the solution of hidden profiles even if one of the other members favors the correct alternative. Finally, Experiment 4 replicated these results in face-to-face interacting 3-person groups.